Molecular profiling of Vitis vinifera Chardonnay obtained by somatic embryogenesis - Christophe Bertsch; Flore Kieffer; Cécile Triouleyre; Gisèle Butterlin; Didier Merdinoglu; Bernard Walter (OENO one, 2003)
With the help of microsatellite profiling, we showed that Vitis vinifera Chardonnay clone 96 is a periclinal chimera plant which is composed at least of two distinct cell layers. Performing somatic embryogenesis allowed us to separate the two cell layers and to regenerate L1 plants. These regenerated L1 plants did not show phenotypic differences to the parental clone when grown in greenhouse conditions, suggesting therefore that the phenotype of Chardonnay 96 did not result of an interaction between the two distinct cell layers L1 and L2.